Birzhan Sal – Outstanding Representative of the Singing Tradition of Sary-Arka - Baibek, А.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
The article is aimed to reveal the individuality of the outstanding representative of Arka song tradition – an akyn-improviser, a singer-composer Birzhan Kozhagylule (1834-1897). For a deeper understanding of his song heritage, assessment of his greatness, talent and innovation an end-toend method of research was chosen: consideration of the features of the figurative and poetic system and characteristic features of his musical-poetic style. Themes and ideological basis of Birzhan Sal’s creativity represents the following traditional thematic series, inherent to all sals and seri: arnau ander – songs dedicated to girls, created by young sal as a tribute to tradition; koshtasu ander – songs of the farewell cycle about an irretrievably gone youth and the osiet ander - songs of parting words and wishes to children and descendants. The principal novelty of the poetics of his songs introduced the akyn ritual of tanystyru to his songs, emphasizing the high significance of the author’s personality and his individualized style. Songs of a social and ethical orientation that reflect the civic position of the singer are instant improvisations and an emotional response to real events. A harmonious combination of brilliant vocal skills and akyn oratory in the creative nature of Birzhan has determined his style as a synthesis of emotional love lyrics of sals and sery with intellectuality and civicism of akyns. Musical style represents large-scale song forms, where the main thing in the chorus part is the “sung” thought and a considerable alexic chorus as an expression of special lyricism. Turning to the form making patterns of the traditional “Kara olen” is associated with the ideologicalfigurative content of his songs. These are lyrical ansau-sagynish ander – songs of melancholy and dreams, as well as mun-sher ander – songs of loss associated with tragedy at the end of life. An innovative form-building technique is shown through the asynchrony of verse and tune that occurs only in the “Temirtas” song, which stands apart in his work. The new synthesizing genre anngіme – song-story and the power of his dramatic sorrowful-tragic monologue, which lies in the ritual origins of the intonational-melodic canvas of the song, is certainly a composing masterpiece not only of Birzhan sal’s heritage, but of the heritage of the whole Arka song culture.